Ocean bottom seismic noise : applications for the crust knowledge, interaction ocean-atmosphere and instrumental behaviour - Corela, Carlos (2016)
Tese de doutoramento, Ciências Geofísicas e da Geoinformação (Geofisíca), Universidade de Lisboa, Faculdade de Ciências, 2014